Navigating the Labyrinth of Motivation: Students’ Subjective Experiences in Arabic Language Learning - Muhammad An Naufar Prastyo; Yeni Maratus Solekah (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2025)
This phenomenological study explores the subjective experiences and motivational labyrinth of students learning Arabic language at SMP Muhammadiyah 6 Ngawi. Through in-depth interviews with 12 participants and classroom observations, this research investigates how students navigate their motivational journey in Arabic language learning, uncovering the complex interplay between intrinsic and extrinsic factors, challenges, and coping strategies. Using Braun and Clarke’s thematic analysis, four main themes emerged: (1) Religious and Cultural Connectivity (students’ deep connection to Islamic identity and desire to understand religious texts), (2) Academic and Social Pressures (external demands from family, school expectations, and peer influences), (3) Linguistic Complexity and Learning Barriers (challenges in Arabic grammar, pronunciation, and limited practice opportunities), and (4) Adaptive Resilience and Support Systems (strategies students develop to overcome obstacles and maintain motivation). The findings reveal that Arabic language learning motivation is a dynamic, multifaceted phenomenon influenced by students’ religious identity, social environment, and individual learning experiences. These insights contribute to understanding motivation in second language acquisition within Islamic educational contexts and provide implications for pedagogical approaches in Arabic language teaching.